2019
DOI: 10.1177/2047487319845314
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in synthetic pharmacotherapies for dyslipidaemias

Abstract: Despite the demonstrated benefits of statins and injectable biologics, there is a need for new and safe oral agents for addressing classical lipid targets, low-density lipoprotein cholesterol (LDL-C), triglycerides and high-density lipoprotein cholesterol (HDL-C). LDL-C is unquestionably causal in the development of atherogenesis and atherosclerotic cardiovascular disease, but new options are required to address triglyceride-rich lipoproteins and lipoprotein(a). For hypercholesterolaemia, pitavastatin provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 142 publications
(207 reference statements)
0
19
0
1
Order By: Relevance
“…In the present issue of the journal the review by Sirtori et al, revisiting available English-language studies published from January 1998 to March 2019, investigates synthetic orally administered pharmacotherapies, in advanced development or currently in use. 4 In brief, the authors showed that among the novel cholesterol-lowering medications, pitavastatin and bempedoic acids are promising agents because the former does not adversely affect glucose metabolism and the latter is not associated with muscular side effects confirming the results of a recent review. 5 In the context of hypertriglyceridemia pemafibrate, a selective PPARa modulator, exhibited a relatively significant lower elevation in serum creatinine and liver function tests.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…In the present issue of the journal the review by Sirtori et al, revisiting available English-language studies published from January 1998 to March 2019, investigates synthetic orally administered pharmacotherapies, in advanced development or currently in use. 4 In brief, the authors showed that among the novel cholesterol-lowering medications, pitavastatin and bempedoic acids are promising agents because the former does not adversely affect glucose metabolism and the latter is not associated with muscular side effects confirming the results of a recent review. 5 In the context of hypertriglyceridemia pemafibrate, a selective PPARa modulator, exhibited a relatively significant lower elevation in serum creatinine and liver function tests.…”
mentioning
confidence: 60%
“…In the present issue of the journal the review by Sirtori et al., revisiting available English-language studies published from January 1998 to March 2019, investigates synthetic orally administered pharmacotherapies, in advanced development or currently in use. 4…”
Section: Recent Advances In Synthetic Pharmacotherapies For Dyslipidamentioning
confidence: 99%
“…HDL, removing cholesterol from the arterial walls by way of the transporters ABCA1 and ABCG1 can effectively raise HDL-cholesterol back-transport as a mechanism of arterial protection [42]. However, this is now rated as just one of several protective mechanisms and, interestingly, drugs raising HDL-C do improve cholesterol efflux, but this is not always associated with a reduced CV risk (CETP antagonists) [44]. HDL is responsible for key effects on macrophage induced inflammation and reduced endoplasmic reticulum (ER) stress and apoptosis [45,46] and the same membrane transporters can control monocyte activation, adhesiveness and inflammation.…”
Section: Hdlthe Present Day Biologymentioning
confidence: 99%
“…Thus, the association between elevated small LDL, low HDL-C, and high TGs bring about “atherogenic dyslipidemia,” which markedly raises CV risk and for which different therapeutic strategies have been developed [3]. While treatment of hypercholesterolemia can be successfully handled with drugs targeting cholesterol biosynthesis [4], MetS is characterized by a number of diverse metabolic abnormalities that are more difficult to pursue. Control of the metabolic syndrome and atherogenic dyslipidemia may be achieved by the agonists of the family of peroxisome proliferator-activator receptors (PPARs), i.e., nuclear-hormone receptors and transcription factor activating ligands, discovered in the early 1990s [5], and potentially involved in the development of CVD and metabolic disorders such as diabetes and inflammatory diseases [6].…”
Section: Introductionmentioning
confidence: 99%